Molecular characterization of India isolates of Pasteurella multocida serotype B:2 using REA, RAPD-PCR and ribotyping - DUTTA, T K; GAUTAM, RAJEEV; SINGH, V P; KUMAR, A A (The Indian Journal of Animal Sciences, 2014)
Pasteurella multocida (serotype B:2) isolates (35) from different animals were tested for differentiation by restriction endonuclease analysis (REA), ribotyping and randomly amplified polymorphic-DNC (RAPD)-PCR analysis. Reproducible patterns were obtained from all the 3 methods. All the isolates were found similar phenotypically, as well as genotypically irrespective of their hosts and genographical locations. All the strains were also similar with the standard vaccine strain (P52 Izatnagar) used in India. Two specific bands were observed at 8.4-71 kb range having diagostic value for B:2 sertype when digests with enzyme Hha I, which were absent in other serotypes.